Comparing Yield, Quality, Water Use Efficiency, and Value between Fodder and Grain Produced Using Ridge‐Furrow Rainwater Harvesting in a Semiarid Region. Issue 5 (15th August 2019) - Wang, Qi; Zhang, Dengkui; Zhou, Xujiao; Liu, Jianrong; Liu, Qinglin; Li, Xiaoling; Sample, David J.; Zhang, Yongsheng; Zhang, Rui
Abstract : Agriculture production in study areas benefits from the use of ridge‐furrow rainwater harvesting (RFRH) to supplement rainfall in the absence of irrigation from imported sources. However, it is necessary to select suitable fodder plants for use with RFRH in this climate. In this paper, 10 treatments (3 ridge widths × 3 ridge‐mulching materials + flat planting [FP] as control) in a complete random design were applied in a 3‐yr field experiment for alfalfa ( Medicago sativa L.) and oat ( Avena sativa L.) production, respectively. Ridges mulched with plastic film (PF) and ridges mulched with biodegradable film (BF) had positive effects on fodder, grain yields, and water use efficiency (WUE), but ridges with manually compacted soil (MCS) had a negative effect on yield and WUE in the most cases. Fodder, grain yields, and WUE decreased as ridge width increased. For oats, the decrease of WUE of MCS was 1.31 kg ha −1 mm −1, but the increase of WUE of BF and PF was 0.83 and 1.25 kg ha −1 mm −1, respectively, compared with that of FP over 3 yr. For alfalfa, the increase of WUE of MCS, BF, and PF was, respectively, 0.22, 5.62, and 6.33 kg ha −1 mm −1 . The RFRH systems, especially PF and BF, produced oat and alfalfa fodders with increased crude protein content and decreased acid and neutral detergent fiber content. The average alfalfa fodder yield was 1.37 times greater than that of oats, whereas the average WUE of alfalfa was 2.62 times greater than that of oats. Alfalfa fodder contained higher crude proteins and lower neutral detergent fiber content than oat fodder and had similar acid detergent fiber. It is more economic to harvest oat fodder than to harvest oat grain, and it is more economic to produce alfalfa than to produce oats.